Revisiting the role of external debt in economic growth of developing countries - Mohd Daud S.N.; Podivinsky J.M. (2024)
This paper proposes a study on the contribution of external debt to the expansion of economic growth for 31 developing countries. Over a period of 36 years, by using dynamic panel data econometrics estimation GMM-system, the results reveal that the accumulation of external debt is associated with a slowdown in the economies of the developing countries. In addition, this paper finds evidence that debt service ratio does not crowd out the investment rate in developing countries. In other words, even though external debt is negatively associated with economic growth, countries are found to be safe from being in the debt overhang hypothesis. Furthermore, there is evidence to support the existence of spatial dependence in the growth model, suggesting the existence of a positive spillover effect of growth among the neighbouring countries. 2012 Copyright Vilnius Gediminas Technical University (VGTU) Press Technika.